Metal laminated film and its manufacturing method
By using surface activation bonding to laminate metal layers on liquid crystal polymer films without heating above their melting point, the method enhances transmission and bonding strength, addressing the issues of dielectric property deterioration and high-frequency performance in existing metal laminated films.
Patent Information
- Application Number
- JP2020075910
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-04-22
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-04-22
AI Technical Summary
Existing metal laminated films, particularly those using thermal lamination methods, suffer from deterioration of dielectric properties and transmission characteristics due to heating liquid crystal polymer films near or above their melting point, leading to disturbed molecular orientation and poor high-frequency performance.
A method involving surface activation bonding is employed to laminate a metal layer onto a liquid crystal polymer film, maintaining the film below its melting point, with specific orientation control and intermediate layers to enhance adhesion and reduce dielectric loss.
The method improves transmission characteristics and bonding strength, ensuring reliable fine wiring and high-frequency performance of printed wiring boards.
Smart Images

Figure 0007618390000008 
Figure 0007618390000009 
Figure 0007618390000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal laminated film and a method for producing the same. [Background technology]
[0002] Conventionally, metal laminated films in which a metal layer such as copper foil is laminated onto a rigid substrate such as a paper-based phenolic resin or a polymer film such as a liquid crystal polymer film have been known as substrates for producing printed wiring boards. In recent years, in preparation for the arrival of the fifth generation mobile communication system (5G), development of metal laminated films in which a metal layer such as copper foil is laminated onto a liquid crystal polymer film with low dielectric properties has been progressing in order to improve the high frequency characteristics of printed wiring boards.
[0003] Metal laminated films are generally known to be produced by a thermal lamination method in which a metal foil with a roughened surface is heated and pressed against a polymer film in terms of adhesion. For example, Patent Document 1 discloses a high-frequency circuit board in which the molecular orientation degree SOR of the liquid crystal polymer film is 1.3 or less, and the high-frequency circuit board is produced by using a thermal lamination method to heat and press a rolled copper foil against the liquid crystal polymer film. Patent Document 2 discloses a laminate for flexible printed wiring boards produced by continuously supplying a liquid crystal polymer film and a copper foil with a specified surface roughness Rz of the pressing surface, heating the liquid crystal polymer film to a temperature above the melting point, and heat-pressing the copper foil against the liquid crystal polymer film using a thermal lamination method.
[0004] Meanwhile, there are also known metal laminate films that are produced using surface activation bonding, in which the surface of a laminate is activated by removing oxides, dirt, and the like by a method such as sputter etching, and the activated surface of the laminate is brought into contact with the surface of another laminate and rolled to bond them. For example, Patent Document 3 discloses a multi-layer metal laminate film produced by pressing a metal thin film surface activated by sputter etching in a metal thin film laminate film having a metal thin film formed on the surface of a polymer film against a metal foil surface, as a metal laminate film intended for use in flexible circuit boards and the like. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2000-269616 A [Patent Document 2] Patent No. 5411656 [Patent Document 3] Patent No. 4532713 Summary of the Invention [Problem to be solved by the invention]
[0006] When a metal layer is heat-pressed onto a liquid crystal polymer film to produce a metal laminated film using the thermal lamination method disclosed in Patent Documents 1 and 2, it is necessary to heat the liquid crystal polymer film to a temperature above its melting point. As a result, the liquid crystal polymer film is heated to a temperature near or above its melting point, and as a result, the film may be significantly altered and its orientation may be significantly disturbed. This may lead to deterioration of the dielectric properties of the liquid crystal polymer film, and the transmission properties of a printed wiring board produced from the metal laminated film may be reduced.
[0007] On the other hand, in the multilayer metal laminate film disclosed in Patent Document 3, which is a metal laminate film produced by surface activated bonding, a liquid crystal polymer film is not used in the polymer film, and therefore the printed wiring board produced therefrom has poor transmission characteristics, particularly in the high frequency range (e.g., 28 GHz).
[0008] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, a primary object of the present invention is to provide a metal laminated film capable of improving the transmission characteristics of a printed wiring board, and a method for producing the same. [Means for solving the problem]
[0009] As a result of intensive research, the present inventors have found that when a liquid crystal polymer film is used as the polymer film of a metal laminated film, the metal laminated film can be produced by bonding a metal layer to the liquid crystal polymer film by surface activated bonding, thereby suppressing the disorder of the orientation of the liquid crystal polymer film and solving the above problems, and have completed the invention. That is, the gist of the present invention is as follows.
[0010] (1) A metal laminated film, comprising a liquid crystal polymer film having a metal layer laminated on at least one surface thereof, the liquid crystal polymer film having a degree of orientation F of 0.31 or more at a central portion in the thickness direction. (2) A metal laminated film characterized in that a metal layer is laminated on at least one surface of a liquid crystal polymer film, and the orientation degree F of the central portion in the thickness direction of the liquid crystal polymer film is 77% or more of the orientation degree F of the central portion in the thickness direction of the liquid crystal polymer film before the metal layer is laminated. (3) The metal laminated film according to (1) or (2) above, wherein the average degree of orientation F in the thickness direction of the liquid crystal polymer film is 0.31 or more. (4) A metal laminated film described in any one of (1) to (3) above, characterized in that the dielectric tangent of the liquid crystal polymer film is less than 114% of the dielectric tangent of the liquid crystal polymer film before the metal layer is laminated thereto. (5) The metal laminated film according to any one of (1) to (4) above, wherein the bonding strength between the metal layer and the liquid crystal polymer film is 2.0 N / cm or more. (6) The metal laminated film according to any one of (1) to (5) above, wherein the metal layer has a metal foil. (7) The metal laminated film according to (6) above, wherein the metal layer further comprises an intermediate layer containing a metal between the liquid crystal polymer film and the metal foil. (8) The metal laminated film according to (7) above, characterized in that the intermediate layer contains any one metal selected from the group consisting of copper, iron, nickel, zinc, chromium, cobalt, titanium, tin, platinum, silver, and gold, or an alloy containing such a metal. (9) The metal laminated film according to any one of (6) to (8), wherein the metal foil is a copper foil, a copper alloy foil, or a copper foil with a carrier. (10) A method for producing a metal laminated film as described in (7) above, comprising the steps of: preparing a liquid crystal polymer film and a metal foil (preparation step); laminating an intermediate layer containing a metal on at least one surface of the liquid crystal polymer film (intermediate layer lamination step); activating the surface of the intermediate layer by sputter etching (activation step); activating the surface of the metal foil by sputter etching (activation step); rolling-bonding the activated surfaces of the intermediate layer and the metal foil together at a rolling reduction of 0 to 30% (rolling-bonding step); and subjecting the roll-bonded intermediate layer and the metal layer having the metal foil and the liquid crystal polymer film to a heat treatment at a temperature of not less than the melting point of the liquid crystal polymer film -100°C and not more than the melting point -10°C (heat treatment step). (11) The method for producing a metal laminated film according to (10) above, wherein the liquid crystal polymer film after the heat treatment has a degree of orientation F of 0.31 or more at a central portion in the thickness direction. (12) A method for producing a metal laminated film as described in (10) or (11) above, characterized in that the orientation degree F of the central part in the thickness direction of the liquid crystal polymer film after the heat treatment is 77% or more of the orientation degree F of the central part in the thickness direction of the liquid crystal polymer film before the metal layer is laminated thereto. (13) A method for producing a metal laminated film described in any one of (10) to (12) above, characterized in that the dielectric tangent of the liquid crystal polymer film after the heat treatment is less than 114% of the dielectric tangent of the liquid crystal polymer film before the metal layer is laminated thereto. Effect of the Invention
[0011] According to the present invention, the transmission characteristics of a printed wiring board can be improved. [Brief description of the drawings]
[0012] [Figure 1] 1 is a schematic cross-sectional view showing an example of a metal laminated film according to an embodiment. [Figure 2A] 1 is a schematic cross-sectional view showing a main part of an example of a method for producing a metal laminated film according to an embodiment. [Figure 2B] 1 is a schematic cross-sectional view showing a main part of an example of a method for producing a metal laminated film according to an embodiment. [Diagram 3] 1 is a schematic diagram showing a measurement area of the degree of orientation F in a slice of a liquid crystal polymer film. [Figure 4] 1 is a graph showing the degree of orientation F at each position of the measurement area in slices of an untreated liquid crystal polymer film and slices of Example 1 and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments of the metal laminated film and the method for producing the same of the present invention will be described.
[0014] A. Metal laminated film Here, the metal laminated film of the present invention will be described by way of example with reference to Fig. 1. Fig. 1 is a schematic cross-sectional view showing one example of the metal laminated film of the embodiment.
[0015] 1, the metal laminated film 1A of this example has a metal layer 10 laminated on one surface 20a of a liquid crystal polymer film 20. The metal layer 10 has an intermediate layer 14 containing copper laminated on one surface 20a of the liquid crystal polymer film 20, and a copper foil (metal foil) 12 laminated on a surface 14a of the intermediate layer 14 opposite to the liquid crystal polymer film 20 side.
[0016] The orientation degree F of the central portion in the thickness direction of the liquid crystal polymer film 20 before the metal layer 10 is laminated is 0.4. In contrast, in the metal laminated film 1A, the orientation degree F of the central portion in the thickness direction of the liquid crystal polymer film 20 is 0.31 or more, which is 77% or more of the orientation degree F of the central portion in the thickness direction of the liquid crystal polymer film 20 before the metal layer 10 is laminated. As a result, the dielectric loss tangent of the liquid crystal polymer film 20 is less than 114% of the dielectric loss tangent of the liquid crystal polymer film 20 before the metal layer 10 is laminated. Therefore, the transmission characteristics of the printed wiring board made from the metal laminated film 1A can be improved. Furthermore, the bonding strength between the metal layer 10 and the liquid crystal polymer film 20 is 2.0 N / cm or more, and the adhesion between the metal layer 10 and the liquid crystal polymer film 20 is high. Therefore, the reliability of the fine wiring of the printed wiring board made from the metal laminated film 1A can be improved.
[0017] Therefore, the metal laminated film of the embodiment can improve the transmission characteristics of the printed wiring board, similarly to the metal laminated film 1A of the above example. Furthermore, when the bonding strength between the metal layer and the liquid crystal polymer film is 2.0 N / cm or more, the transmission characteristics of the printed wiring board and the reliability of the fine wiring can be achieved at the same time.
[0018] Next, each component of the metal laminated film of the embodiment will be described in detail.
[0019] 1. Liquid crystal polymer film The degree of orientation F at the central portion in the thickness direction of the liquid crystal polymer film is 77% or more of the degree of orientation F at the central portion in the thickness direction of the liquid crystal polymer film before the metal layer is laminated.
[0020] Here, the term "liquid crystal polymer film" refers to a film made of an aromatic polyester resin having parahydroxybenzoic acid or the like as a basic structure, which exhibits liquid crystal properties in a molten state.
[0021] Here, "degree of orientation F" refers to the degree of molecular orientation in MD (direction of film stretching), and is calculated using the following method. First, a polarizer for infrared light is attached to a micro-infrared spectrometer (micro-FT-IR device), and the infrared transmission spectrum of a polymer film (here, a liquid crystal polymer film) in the polarization direction parallel to the MD and the infrared transmission spectrum in the polarization direction perpendicular to the MD are measured. Next, the 1601 cm -1 The infrared dichroic ratio D (1601 cm of the infrared transmission spectrum with polarization direction parallel to MD) was calculated using the peak -1 The intensity of the peak A∥ at 1601 cm in the infrared transmission spectrum with polarization perpendicular to the MD -1 The ratio of the peak intensities A⊥ of the peaks in the infrared transmission spectrum is calculated. -1 and 1572.4 cm -1 Set it to a straight line connecting 1601cm -1 The peak is attributed to the C=C stretching vibration of the benzene ring and has a transition moment parallel to the molecular chain. Next, the degree of orientation F is calculated from the infrared dichroic ratio D. The calculation methods for the infrared dichroic ratio D and the degree of orientation F are formulas (1) and (2), respectively.
[0022]
number
number
[0023] The "orientation degree F at the center in the thickness direction" refers to, for example, an orientation degree F calculated from the infrared dichroic ratio D measured in a measurement region located at the center in the thickness direction in a cross section (vertical cross section) perpendicular to the surface of the liquid crystal polymer film and parallel to the MD. The measurement region is not particularly limited, and examples thereof include a rectangular region having a MD length of 100 μm and a thickness length of 10 μm as shown in FIG. 3.
[0024] The "liquid crystal polymer film before a metal layer is laminated" refers to a liquid crystal polymer film prepared in the preparation step described in the section "B. Metal laminated film manufacturing method 1. Preparation step" below.
[0025] The orientation degree F of the central part in the thickness direction of the liquid crystal polymer film is not particularly limited as long as it is 77% or more of the orientation degree F of the central part in the thickness direction of the liquid crystal polymer film before the metal layer is laminated, and it is preferable that it is closer to the orientation degree F of the central part in the thickness direction of the liquid crystal polymer film before the metal layer is laminated, specifically, for example, 0.31 or more, more preferably 0.315 or more, and further preferably 0.32 or more, because the transmission characteristics become particularly good.
[0026] The average of the orientation degree F in the thickness direction of the liquid crystal polymer film is not particularly limited, and is preferably closer to the average of the orientation degree F in the thickness direction of the liquid crystal polymer film before the metal layer is laminated, but is preferably 79% or more of the average of the orientation degree F in the thickness direction of the liquid crystal polymer film before the metal layer is laminated. This is because the transmission characteristics become good. Specifically, the average of the orientation degree F in the thickness direction of the liquid crystal polymer film is preferably, for example, 0.31 or more, more preferably 0.315 or more. This is because the transmission characteristics become particularly good.
[0027] Here, the "average orientation degree F in the thickness direction" refers to, for example, the average value of multiple orientation degrees F calculated from the infrared dichroic ratio D measured in multiple measurement regions (e.g., five or more measurement regions) obtained by equally dividing an area of a predetermined MD length in a cross section (vertical cross section) perpendicular to the surface of the liquid crystal polymer film and parallel to the MD in the thickness direction. Note that the multiple measurement regions are not particularly limited, and examples thereof include five rectangular regions located at thickness direction distances of 5 μm, 15 μm, 25 μm, 35 μm, and 45 μm from the surface as shown in FIG. 3.
[0028] The dielectric loss tangent of the liquid crystal polymer film is not particularly limited, and is preferably closer to the dielectric loss tangent of the liquid crystal polymer film before the metal layer is laminated, for example, less than 114% of the dielectric loss tangent of the liquid crystal polymer film before the metal layer is laminated, and more preferably less than 112% of the dielectric loss tangent of the liquid crystal polymer film before the metal layer is laminated, and more preferably less than 110%. This is because the transmission characteristics are good. Specifically, the dielectric loss tangent of the liquid crystal polymer film is preferably less than 0.0024, for example. This is because the transmission characteristics are particularly good.
[0029] Here, the "dielectric loss tangent" refers to the dielectric loss tangent around 28 GHz, for example, measured by the open resonator method using a relative dielectric constant / dielectric loss tangent measuring system (DPS03 manufactured by Keycom Corporation) at a measurement frequency of 28 GHz.
[0030] The thickness of the liquid crystal polymer film can be appropriately set depending on the application of the metal laminate film. For example, when used as a flexible printed circuit board, the thickness is preferably 10 μm or more and 150 μm or less, more preferably 10 μm or more and 120 μm or less. The thickness of the liquid crystal polymer film can be measured by a micrometer or the like, and refers to the average value of the thickness measured at 10 points randomly selected from the surface of the liquid crystal polymer film. In addition, for the liquid crystal polymer film, the deviation from the average value of the measured values at 10 points is preferably within 20% for all measured values, more preferably within 15%.
[0031] 2. Metal layer The metal layer is not particularly limited as long as it has a metal foil, and may further have an intermediate layer containing a metal between the liquid crystal polymer film and the metal foil in addition to the metal foil, as in the metal layer 10 in the metal laminated film 1A shown in Fig. 1, or may be the metal foil, but is preferably further having an intermediate layer containing a metal between the liquid crystal polymer film and the metal foil in addition to the metal foil. Hereinafter, the metal foil of the metal layer and the intermediate layer when the metal layer has an intermediate layer and a metal foil will be described.
[0032] (1) Metal foil The metal foil varies depending on the application of the metal laminated film and is not particularly limited, but examples thereof include single-layer foils such as copper foil, nickel foil, aluminum foil, and iron foil, laminated foils (clad materials) thereof, alloy foils, rolled thin sheets, and the like. As the metal foil, copper foil or copper alloy foil is preferable. This is because, for example, a flexible substrate for forming fine wiring can be obtained by rolling and bonding these to the liquid crystal polymer film. In addition, when preparing a flexible substrate for forming finer wiring, it is preferable to use a carrier-attached copper foil consisting of an ultra-thin copper foil, a peeling layer, and a carrier layer as the metal foil. When using a carrier-attached copper foil, the carrier-attached copper foil is laminated so that the ultra-thin copper foil, the peeling layer, and the carrier layer are arranged in this order from the liquid crystal polymer film side or the intermediate layer side. The carrier-attached copper foil is not particularly limited, but examples thereof include MT18FL manufactured by Mitsui Mining & Smelting Co., Ltd. and JXUT-III manufactured by JX Metals Corporation.
[0033] The thickness of the metal foil varies depending on the use of the metal laminate film and is not particularly limited, but for example, for flexible printed wiring board use, it is preferably 3 μm to 100 μm, and more preferably 10 μm to 35 μm. When a copper foil with a carrier layer is used as the metal foil, the thickness of the ultra-thin copper foil is not particularly limited, but is preferably, for example, 0.5 μm to 10 μm, and more preferably 1 μm to 7 μm. In addition, the thickness of the release layer is not particularly limited, but is preferably, for example, 1 nm to 1 μm, and the thickness of the carrier layer is not particularly limited, but is preferably, for example, 10 μm to 100 μm.
[0034] Although not shown in FIG. 1, the metal layer may further include at least one of a roughening particle layer, an anticorrosive layer, and a treatment layer with a silane coupling agent (hereinafter, sometimes referred to as a "treatment layer") on the surface of the metal foil on the liquid crystal polymer film side. The treatment layer may be a laminate of any one layer, or a laminate of multiple layers. The roughening particle layer may include, for example, any one metal selected from the group consisting of Cu, Co, and Ni, or an alloy thereof, but is not limited thereto. Specific examples include a cobalt-nickel alloy plating layer, a copper-cobalt-nickel alloy plating layer, and the like. The anticorrosive layer may include, for example, any one metal selected from the group consisting of Cr, Ni, and Zn, or an alloy thereof, but is not limited thereto. Specific examples include a chromium oxide coating, a mixture coating of chromium oxide and zinc / zinc oxide, and a Ni plating layer. Further, examples of the silane coupling agent include, but are not limited to, olefin-based silanes, epoxy-based silanes, acrylic-based silanes, amino-based silanes, and mercapto-based silanes. The silane coupling agent can be applied by a suitable method such as spraying, coating with a coater, or immersion.
[0035] (2) Middle Class The intermediate layer is not particularly limited as long as it is a layer containing a metal, and may be a single layer containing a metal or a laminate of two or more layers containing a metal. Examples of the intermediate layer include a layer formed by sputtering, vapor deposition, or electroless plating on the liquid crystal polymer film.
[0036] The intermediate layer is not particularly limited as long as it contains a metal, but it is preferable that it contains any one of metals selected from the group consisting of copper, iron, nickel, zinc, chromium, cobalt, titanium, tin, platinum, silver, gold, aluminum, palladium, and zirconium, or an alloy containing the metal. The intermediate layer may also be a laminate of multiple layers containing a metal. In particular, when the metal foil is a copper foil or a copper alloy foil, the intermediate layer is also preferably one containing copper or a copper alloy such as a copper-nickel alloy, and among these, it is preferable that it contains a metal having the same composition as the metal foil. This is because etching becomes easier.
[0037] When the intermediate layer is, for example, a Cu-Ni alloy, the ratio of Ni to Cu is preferably 10 to 90% in at%. However, this is not limited thereto. By providing an intermediate layer, not only can the surface of the metal foil or liquid crystal polymer film be protected and the adhesion between the metal foil and the liquid crystal polymer film be improved, but also a function specific to the intermediate layer can be imparted (for example, a function as an etching stopper layer during etching). The thickness of the intermediate layer may be any thickness that can exhibit the function of improving adhesion, and is not particularly limited, but is, for example, preferably 5 nm or more and 200 nm or less, and more preferably 10 nm or more and 100 nm or less.
[0038] 3. Metal laminated film In the metal laminated film, although there is no particular limitation, it is preferable that the bonding strength between the metal layer and the liquid crystal polymer film is 2.0 N / cm or more, as in the metal laminated film 1A shown in Fig. 1. This is because the reliability of the fine wiring of the printed wiring board can be improved.
[0039] In order to measure the value of the bonding strength, a test piece is first prepared from the metal laminated film, and a 1 cm wide cut is made in the metal layer using a knife or the like. Then, after the metal layer and the liquid crystal polymer film are partially peeled off, the liquid crystal polymer film is fixed to a support, and the metal layer is pulled in a 90° direction with respect to the liquid crystal polymer film at a speed of 50 mm / min. The force required for peeling at this time is taken as the bonding strength (unit: N / cm). In addition, if the metal layer is thin and fragile, it may be broken when measuring the bonding strength. In that case, the bonding strength may be measured after electrolytic plating or the like (for example, copper plating when the metal layer is copper) is applied to the surface of the metal layer to increase the thickness of the metal layer to about 5 to 50 μm. The method for measuring the value of the bonding strength is the measurement method specified in JIS C6471.
[0040] In this specification, the term "bonding strength between a metal layer and a liquid crystal polymer film" refers not only to the bonding strength when peeling occurs at the interface between the metal layer and the liquid crystal polymer film, but also to the bonding strength when peeling occurs due to internal destruction of the metal layer, and the bonding strength when peeling occurs due to internal destruction of the liquid crystal polymer film.
[0041] The metal laminate film can be used as a metal-clad laminate for producing a flexible printed circuit board.
[0042] A printed wiring board having fine wiring formed thereon can be obtained by using a metal laminate film. In the process of forming wiring, an additional metal layer can be formed only on the wiring portion. Specifically, a printed wiring board can be obtained by appropriately using a conventionally known method such as a modified semi-additive method (MSAP method), a semi-additive method (SAP method), or a subtractive method. For example, when the modified semi-additive method (MSAP method) is used, a printed wiring board can be manufactured by masking non-wiring portions on a metal layer in a metal laminate film, forming an additional metal layer by copper plating on the unmasked portions, removing the mask, and removing the metal layer hidden by the mask by etching. Note that the "printed wiring board" in the present invention includes not only a laminate having wiring formed thereon, but also a board on which electronic components such as ICs are mounted after wiring is formed.
[0043] In the metal laminated film 1A shown in Fig. 1, a metal layer is laminated on one surface of the liquid crystal polymer film, but the metal laminated film is not limited to this. That is, if necessary, a metal layer may be provided on both surfaces of the liquid crystal polymer film. By using a metal laminated film in which metal layers are provided on both surfaces of the liquid crystal polymer film, a flexible printed circuit board in which wiring is formed on both surfaces of the liquid crystal polymer film can be obtained.
[0044] B. Manufacturing method of metal laminated film Here, an embodiment of the method for producing a metal laminated film of the present invention will be described by way of example. Figures 2A and 2B are schematic cross-sectional views showing a main part of one example of the method for producing a metal laminated film of the embodiment.
[0045] In the manufacturing method of the metal laminated film of this example, first, a liquid crystal polymer film and a copper foil (metal foil) are prepared. The orientation degree F of the central part in the thickness direction of the liquid crystal polymer film is 0.4.
[0046] Next, as shown in Fig. 2A(a), one surface 20a of the liquid crystal polymer film 20 is activated by sputter etching at room temperature using an activation treatment device (not shown). Then, as shown in Fig. 2A(b), an intermediate layer 14 containing copper is sputter-formed on the surface 20a of the activated liquid crystal polymer film 20 at room temperature using a sputtering device (not shown).
[0047] Next, as shown in FIG. 2A(c), using an activation bonding apparatus (not shown), at room temperature, the surface 14a of the intermediate layer 14 is activated by sputter etching, the surface 12a of the copper foil 12 is activated by sputter etching, and the activated surfaces of the intermediate layer 14 and the copper foil 12 are roll-bonded together at a reduction ratio of 0 to 30%.
[0048] Next, as shown in Fig. 2B(d), the metal layer 10 having the roll-bonded intermediate layer 14 and copper foil 12 and the liquid crystal polymer film 20 are heat-treated in a heat treatment furnace (not shown) in a vacuum atmosphere or in an inert gas atmosphere such as N2, Ar, or NH gas (e.g., N2 + 5% H2 mixed gas) at a temperature of -100°C to -10°C, which is the melting point of the liquid crystal polymer film 20. This improves the adhesion between the metal layer 10 and the liquid crystal polymer film 20. As a result, a metal laminated film 1A is manufactured as shown in Fig. 2B(e).
[0049] In the manufacturing method of the metal laminated film of this example, the following processes are performed at room temperature: activating the surface 20a of the liquid crystal polymer film 20 by sputter etching, sputter-forming the intermediate layer 14, activating the surfaces of the intermediate layer 14 and the copper foil 12 by sputter etching, and rolling-bonding the activated surfaces of the intermediate layer 14 and the copper foil 12 together. Then, heat treatment is performed at a temperature between the melting point of the liquid crystal polymer film 20 -100°C and the melting point of the liquid crystal polymer film 20 -10°C, thereby improving the adhesion between the metal layer 10 and the liquid crystal polymer film 20. Therefore, unlike the case of producing a metal laminated film using a thermal lamination method, the liquid crystal polymer film 20 is not heated at a temperature near or exceeding the melting point, so that the adhesion between the metal layer 10 and the liquid crystal polymer film 20 can be improved, and the orientation of the liquid crystal polymer film 20 can be prevented from being disturbed, which can prevent the dielectric properties from deteriorating, and the surface morphology of the liquid crystal polymer film 20 from being altered.
[0050] Therefore, according to the manufacturing method of the metal laminated film of the embodiment, as in the manufacturing method of the above example, it is possible to manufacture a metal laminated film in which the adhesion between the metal layer and the liquid crystal polymer film is improved and the deterioration of the dielectric properties is suppressed, and thus it is possible to manufacture a metal laminated film that can achieve both the transmission properties of the printed wiring board and the reliability of the fine wiring.
[0051] Next, each condition of the method for producing the metal laminated film of the embodiment will be described in detail.
[0052] 1. Preparation process The liquid crystal polymer film prepared in the preparation step is not particularly limited, but is preferably one having an orientation degree F of 0.4 or more at the center in the thickness direction, and among them, Vecstar CTQ manufactured by Kuraray Co., Ltd. is preferable because it has a low dielectric tangent and excellent dielectric properties.
[0053] The metal foil prepared in the preparation step is the same as the metal foil explained in the section "A. Metal laminated film 2. Metal layer (1) Metal foil," so a detailed explanation will be omitted here.
[0054] 2. Intermediate layer lamination process The method of laminating the metal-containing intermediate layer on at least one surface of the liquid crystal polymer film in the intermediate layer lamination step is not particularly limited, but for example, a method of activating at least one surface of the liquid crystal polymer film by sputter etching, and then sputter-forming the metal-containing intermediate layer on the activated surface is preferable. The conditions for sputter-forming the film by this method can be appropriately set depending on the metal species constituting the intermediate layer and the thickness of the intermediate layer. The metal species constituting the intermediate layer and the thickness of the intermediate layer are the same as those of the intermediate layer described in the section "A. Metal Laminated Film 2. Metal Layer (2) Intermediate Layer", so the description here is omitted.
[0055] 3.Activation process The sputter etching treatment in the activation step can be performed, for example, by preparing a liquid crystal polymer film provided with a metal foil or intermediate layer to be bonded as a long coil with a width of 100 mm to 600 mm, using the bonding surface of the metal foil or intermediate layer as one electrode grounded to earth, applying an AC current of 1 MHz to 50 MHz between the other electrode supported insulated to generate a glow discharge, and setting the area of the electrode exposed to the plasma generated by the glow discharge to 1 / 3 or less of the area of the other electrode. During the sputter etching treatment, the earthed electrode takes the form of a cooling roll to prevent the temperature of the transported material from rising.
[0056] In the sputter etching treatment in the activation step, the surface to be joined of the metal foil or the liquid crystal polymer film provided with the intermediate layer is sputtered with an inert gas under vacuum to completely remove the adsorbed matter on the surface and to remove a part or all of the oxide layer on the surface. It is preferable to completely remove the copper oxide layer. As the inert gas, argon, neon, xenon, krypton, etc., or a mixed gas containing at least one of these can be applied. Although it depends on the type of metal, the adsorbed matter on the surface of the metal foil and the intermediate layer can be completely removed with an etching amount of about 1 nm, and in particular, the copper oxide layer can be usually removed with an etching amount of about 5 nm to 12 nm (SiO2 equivalent).
[0057] The treatment conditions for sputter etching can be appropriately set depending on the type of metal foil and intermediate layer. For example, the treatment can be performed under vacuum with a plasma output of 100 W to 10 kW and a line speed of 0.5 m / min to 30 m / min. The degree of vacuum at this time is preferably high in order to prevent re-adsorption of substances onto the surface. -5 Pa~10Pa is fine.
[0058] In addition, when a roughened particle layer or an anticorrosive layer is provided on the surface of the metal foil, the surface of the roughened particle layer or the anticorrosive layer is activated by sputter etching. In this case, the roughened particle layer or the anticorrosive layer may be completely removed by sputter etching, or may remain without being removed.
[0059] In addition, the surface of the metal foil or the surface of the intermediate layer before activation by sputter etching may be subjected to Ni plating, chromate treatment, silane coupling agent treatment, etc., as necessary, in order to prevent oxidation or improve adhesion. In addition, the surface of the metal foil may be subjected to a roughening treatment as necessary in order to improve adhesion to the intermediate layer.
[0060] 4. Roll-bonding process The activated surfaces of the metal foil and intermediate layer that have been subjected to sputter etching can be pressed together by roll pressing. The rolling line load of the roll pressing is not particularly limited, and can be set to, for example, a range of 0.1 tf / cm to 10 tf / cm. However, when the thickness of the liquid crystal polymer film provided with the metal foil or intermediate layer before bonding is large, it may be necessary to increase the rolling line load to ensure the pressure during bonding, and the rolling line load is not limited to this numerical range. On the other hand, if the rolling line load is too high, not only the surface layer of the metal foil or intermediate layer but also the bonding interface is likely to deform, so that the thickness accuracy of each layer in the metal laminated film may decrease. In addition, if the rolling line load is high, the processing strain applied during bonding may be large.
[0061] The rolling reduction rate during roll bonding is 0 to 30%, preferably 0 to 15%. The above-mentioned surface activated bonding method can reduce the rolling reduction rate, so that a metal layer with excellent thickness accuracy can be formed without wrinkles or cracks. Furthermore, since the waviness of the interface between the metal foil and the intermediate layer and the liquid crystal polymer film can be reduced, when the metal layer having the metal foil and the intermediate layer is subjected to pattern etching to form wiring, the thickness accuracy is excellent, so that precise wiring can be obtained.
[0062] The bonding by roll pressure bonding is preferably carried out in a non-oxidizing atmosphere, such as a vacuum atmosphere or an inert gas atmosphere such as Ar, in order to prevent a decrease in the bonding strength between the two due to re-adsorption of oxygen onto the metal foil or the intermediate layer surface.
[0063] 5.Heat treatment process The heat treatment temperature is between the melting point of the liquid crystal polymer film -100°C and the melting point of the liquid crystal polymer film -10°C, and preferably between the melting point of the liquid crystal polymer film -70°C and the melting point of the liquid crystal polymer film -20°C. By setting the heat treatment temperature to the lower limit of these ranges or higher, the bonding strength between the metal layer and the liquid crystal polymer film can be improved to a desired strength, and the shape of the metal laminated film curved during roll bonding can be flattened. By setting the heat treatment temperature to the upper limit of these ranges or lower, the orientation of the liquid crystal polymer film can be avoided from being disturbed, and the metal laminated film can be prevented from softening and changing in thickness and width. Since the melting point of the liquid crystal polymer film varies depending on the material, the heat treatment temperature can be appropriately set depending on the material. For example, in the case of Vecstar CTQ (melting point: 310°C) manufactured by Kuraray Co., Ltd., the heat treatment temperature is 210°C to 300°C for the same reason, and preferably 240°C to 290°C.
[0064] The atmosphere in which the heat treatment is performed is not particularly limited, but is preferably a vacuum atmosphere or an inert gas atmosphere such as N2, Ar, or NH gas, and among these, a vacuum atmosphere is preferable, because it is possible to avoid oxidation of the metal layer by the heat treatment and a decrease in the bonding strength between the metal layer and the liquid crystal polymer film.
[0065] The time for the heat treatment is not particularly limited as long as the bonding strength between the metal layer and the liquid crystal polymer film can be made to a desired strength and the orientation of the liquid crystal polymer film can be prevented from being disturbed, but for example, it is preferably 180 seconds or more and 18000 seconds or less, and more preferably 200 seconds or more and 15000 seconds or less. By setting it to the lower limit or more of these ranges, sufficient adhesion between the metal layer and the liquid crystal polymer film can be ensured, and by setting it to the upper limit or less of these ranges, high production efficiency and low cost of the metal laminated film can be realized.
[0066] The heat treatment may be performed, for example, by using a batch-type heat treatment furnace to maintain the metal layer and the liquid crystal polymer film at a desired heat treatment temperature for a desired time in a desired atmosphere (for example, a vacuum atmosphere or an inert gas atmosphere such as N2, Ar, or NH gas). Depending on the heat treatment temperature and atmosphere, the heat treatment may be performed by a roll-to-roll method using a continuous heat treatment furnace. In this case, at least the heating section and the cooling section in the continuous heat treatment furnace are set to a desired atmosphere (for example, a vacuum atmosphere or an inert gas atmosphere such as N2, Ar, or NH gas) and maintained at a desired temperature, and the metal layer and the liquid crystal polymer film are passed through the heating section and the cooling section at a desired speed to maintain the metal layer and the liquid crystal polymer film at the desired heat treatment temperature for a desired time.
[0067] 6.Metal laminated film manufacturing method In the manufacturing method of the metal laminated film of the embodiment, the orientation degree F of the central part in the thickness direction of the liquid crystal polymer film after the heat treatment is preferably 77% or more of the orientation degree F of the central part in the thickness direction of the liquid crystal polymer film before the metal layer is laminated. Specifically, the orientation degree F of the central part in the thickness direction of the liquid crystal polymer film after the heat treatment is preferably 0.31 or more. In addition, the dielectric loss tangent of the liquid crystal polymer film after the heat treatment is preferably less than 114% of the dielectric loss tangent of the liquid crystal polymer film before the metal layer is laminated, and more preferably less than 112% of the dielectric loss tangent of the liquid crystal polymer film before the metal layer is laminated, and more preferably less than 110%.
[0068] Bonding and / or heat treatment under high pressure when producing metal laminated films can significantly change the structure of each layer of the metal laminated film before and after bonding and / or heat treatment, which may impair the properties of the metal laminated film. Therefore, it is preferable to select bonding and heat treatment conditions that can avoid such structural changes. EXAMPLES
[0069] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to these examples.
[0070] Example 1 First, a liquid crystal polymer film having a thickness of 50 μm (Vexstar CTQ-50 manufactured by Kuraray Co., Ltd.) was prepared, and two rolled copper foils having a thickness of 16 μm were prepared as metal foils. Next, both surfaces of the liquid crystal polymer film were activated by sputter etching, and then an intermediate layer (copper layer) (thickness 40 nm) containing copper was sputter-formed on each of the activated surfaces. Next, the surface of one of the intermediate layers and the surface of one of the rolled copper foils were activated by sputter etching, and the activated surface of the rolled copper foil was brought into contact with the activated surface of the intermediate layer, and the activated surfaces of the intermediate layer and the rolled copper foil were roll-bonded to each other with a line load of 1.5 tf / cm. Furthermore, the surface of the intermediate layer on the side where the rolled copper foil was not laminated was activated by sputter etching, and the surface of the other rolled copper foil was activated by sputter etching, and the activated surface of the rolled copper foil was brought into contact with the activated surface of the intermediate layer, and the activated surfaces of the intermediate layer and the rolled copper foil were rolled and bonded together with a line load of 1.5 tf / cm. The rolling reduction was 2.4%. Next, the metal layer having the intermediate layer and the rolled copper foil and the liquid crystal polymer film were subjected to a heat treatment at 250°C for 10,800 seconds in a vacuum atmosphere. As a result, a metal laminated film (layer structure: rolled copper foil / intermediate layer (copper layer) / liquid crystal polymer film / intermediate layer (copper layer) / rolled copper foil) was produced.
[0071] Example 2 First, a liquid crystal polymer film having a thickness of 25 μm (Vexstar CTQ-25 manufactured by Kuraray Co., Ltd.) was prepared, and a rolled copper foil having a thickness of 16 μm was prepared as the metal foil. Next, one surface of the liquid crystal polymer film was activated by sputter etching, and then an intermediate layer (copper layer) (thickness 40 nm) containing copper was sputter-formed on the activated surface. Next, the surface of the intermediate layer and the surface of the rolled copper foil were activated by sputter etching, and the activated surface of the rolled copper foil was brought into contact with the activated surface of the intermediate layer, and the activated surfaces of the intermediate layer and the rolled copper foil were roll-bonded together with a line load of 1.5 tf / cm. The rolling reduction rate was 2.4%. Next, the metal layer having the intermediate layer and the rolled copper foil and the liquid crystal polymer film were subjected to a heat treatment maintained at 280° C. for 10,800 seconds in a vacuum atmosphere. As a result, a metal laminated film (layer structure: rolled copper foil / intermediate layer (copper layer) / liquid crystal polymer film) was produced.
[0072] Example 3 A metal laminated film (layer structure: rolled copper foil / intermediate layer (copper layer) / liquid crystal polymer film) was produced in the same manner as in Example 2, except that the heat treatment after roll bonding was carried out in a N2 atmosphere.
[0073] Example 4 A metal laminated film (layer structure: rolled copper foil / second intermediate layer (copper layer) / first intermediate layer (nickel layer) / liquid crystal polymer film) was produced in the same manner as in Example 3, except that a first intermediate layer (nickel layer) (thickness 40 nm) containing nickel and a second intermediate layer (copper layer) (thickness 40 nm) containing copper were sputter-deposited in that order on one surface of the liquid crystal polymer film as intermediate layers.
[0074] Example 5 First, a liquid crystal polymer film having a thickness of 25 μm (Vexstar CTQ-25 manufactured by Kuraray Co., Ltd.) was prepared, and as a metal foil, a carrier layer having a thickness of 18 μm, a copper-containing carrier layer having a thickness of 1.5 μm was provided via a release layer (organic release layer), and a roughened particle layer and an anti-rust layer were further provided on the surface of the ultrathin copper layer. A carrier layer-attached copper foil (MT18FL manufactured by Mitsui Mining & Smelting Co., Ltd.) was prepared. Next, one surface of the liquid crystal polymer film was activated by sputter etching, and then a copper-containing intermediate layer (copper layer) (thickness 40 nm) was sputter-deposited on the activated surface. Next, the surface of the intermediate layer and the surface of the ultrathin copper layer were activated by sputter etching, and the activated surface of the ultrathin copper layer was brought into contact with the activated surface of the intermediate layer, and the activated surfaces of the intermediate layer and the ultrathin copper layer were roll-bonded to each other with a line load of 1.5 tf / cm. The rolling reduction was 2.4%. Next, the metal layer having the intermediate layer and the copper foil with the carrier layer and the liquid crystal polymer film were subjected to a heat treatment at 250°C for 10,800 seconds in a vacuum atmosphere, thereby producing a metal laminated film (layer structure: copper foil with carrier layer / intermediate layer (copper layer) / liquid crystal polymer film).
[0075] Example 6 A metal laminated film (layer structure: copper foil with carrier layer / intermediate layer (copper layer) / liquid crystal polymer film) was produced in the same manner as in Example 5, except that the metal foil used was a copper foil with a carrier layer in which an ultra-thin copper layer with a thickness of 5.0 μm was provided on a copper-containing carrier layer with a thickness of 18 μm via a release layer (organic release layer), and only an anti-rust layer was provided on the surface of the ultra-thin copper layer, and that the heat treatment after roll bonding was performed at 270°C.
[0076] Example 7 First, a liquid crystal polymer film having a thickness of 25 μm (Vexstar CTQ-25 manufactured by Kuraray Co., Ltd.) was prepared, and as a metal foil, a copper foil with a carrier layer was prepared in which a 2.0 μm-thick ultra-thin copper layer was provided on a carrier layer containing copper having a thickness of 18 μm via a release layer (inorganic release layer), and only a rust-proof layer was provided on the surface of the ultra-thin copper layer. Next, one surface of the liquid crystal polymer film was activated by sputter etching, and then an intermediate layer (copper layer) containing copper (thickness 40 nm) was sputter-formed on the activated surface. Next, the surface of the intermediate layer and the surface of the ultra-thin copper layer were activated by sputter etching, and the activated surface of the ultra-thin copper layer was in contact with the activated surface of the intermediate layer, and the activated surfaces of the intermediate layer and the ultra-thin copper layer were roll-bonded to each other with a line load of 1.5 tf / cm. The rolling reduction rate was 2.4%. Next, the metal layer having the intermediate layer and the copper foil with the carrier layer and the liquid crystal polymer film were subjected to a heat treatment maintained at 280 ° C. for 10,800 seconds in an N2 atmosphere. This produced a metal laminated film (layer structure: copper foil with carrier layer / intermediate layer (copper layer) / liquid crystal polymer film).
[0077] Example 8 A metal laminated film (layer structure: copper foil with carrier layer / second intermediate layer (copper layer) / first intermediate layer (nickel layer) / liquid crystal polymer film) was produced in the same manner as in Example 7, except that a first intermediate layer (nickel layer) (thickness 40 nm) containing nickel and a second intermediate layer (copper layer) (thickness 40 nm) containing copper were sputter-deposited in that order on one surface of the liquid crystal polymer film as intermediate layers.
[0078] Comparative Example 1 A metal laminated film (layer structure: rolled copper foil / liquid crystal polymer film / rolled copper foil) was produced by thermocompression bonding a 12 μm-thick rolled copper foil having a treatment layer made of a roughening particle layer or the like on one side to both surfaces of a 50 μm-thick liquid crystal polymer film (Vexstar CTQ-50 manufactured by Kuraray Co., Ltd.) by a thermal lamination method. The metal laminated film was produced by sandwiching a liquid crystal polymer film between two rolled copper foils so that the surfaces of the treatment layers of the two rolled copper foils were in contact with both surfaces of the liquid crystal polymer film, heating the liquid crystal polymer film to a temperature of 310° C. or higher, and thermocompressing the liquid crystal polymer film and the rolled copper foil to bond the surfaces of the liquid crystal polymer film and the rolled copper foil together.
[0079] Comparative Example 2 A metal laminated film (layer structure: electrolytic copper foil / liquid crystal polymer film / electrolytic copper foil) was produced by thermocompression bonding a 12 μm-thick electrolytic copper foil having a treatment layer made of a roughening particle layer or the like on one side to both surfaces of a 50 μm-thick liquid crystal polymer film (Vexstar CTQ-50 manufactured by Kuraray Co., Ltd.) by a thermal lamination method. The metal laminated film was produced by sandwiching a liquid crystal polymer film between two electrolytic copper foils so that the surfaces of the treatment layers of the two electrolytic copper foils were in contact with both surfaces of the liquid crystal polymer film, heating the liquid crystal polymer film to a temperature of 310° C. or higher, and thermocompressing the liquid crystal polymer film and the electrolytic copper foil to bond the surfaces of the liquid crystal polymer film and the electrolytic copper foil to each other.
[0080] [Orientation degree of liquid crystal polymer film F] The copper layer and electrolytic copper foil were each removed by chemical etching with a ferric chloride solution or the like from the metal laminated films of Example 1 and Comparative Example 2, and slices measuring about 4 μm in the width direction were cut from the liquid crystal polymer film after removal, and the orientation degree F of each region in the thickness direction of each slice was measured. For comparison, slices measuring about 4 μm in the width direction were cut from the same untreated liquid crystal polymer film as that used to prepare the metal laminated films of Example 1 and Comparative Example 2, and the orientation degree F of each region in the thickness direction of the slice was measured. Figure 3 is a schematic diagram showing the measurement region of the orientation degree F in a slice of a liquid crystal polymer film.
[0081] In measuring the degree of orientation F, as shown in Fig. 3, rectangular regions located at distances of 5 μm, 15 μm, 25 μm, 35 μm, and 45 μm in the thickness direction from the surface in a cross section (vertical cross section) perpendicular to the surface of a slice of the liquid crystal polymer film and parallel to the MD were set as measurement regions by an aperture, and the infrared dichroic ratio D was measured by microscopic infrared spectroscopy in each measurement region, and the degree of orientation F was calculated from the infrared dichroic ratio D. The measurement device, measurement method, polarizer, and measurement conditions used are as follows.
[0082] Measurement equipment: Agilent Technologies Cary670 / 620 Measurement method: Polarized light microscopic FT-IR analysis / transmission method Aperture size: MD length 100μm × thickness length 10μm Polarizer: Base material KRS-5 Resolution: 4cm -1 Number of times accumulated: 128 times
[0083] The infrared dichroic ratio D is assigned to the C=C stretching vibration of the benzene ring and has a transition moment parallel to the molecular chain at 1601 cm -1 Specifically, the peak intensity A∥ of the infrared transmission spectrum measured in the polarization direction parallel to the MD and the peak intensity A⊥ of the infrared transmission spectrum measured in the polarization direction perpendicular to the MD were calculated from the peak intensity A of 1601 cm -1 The peak at 1618.9 cm of the spectrum was used as the quantitative peak. -1 and 1572.4 cm -1 The straight line connecting the points was measured as the baseline, and the infrared dichroic ratio D was calculated using formula (1). Furthermore, the degree of orientation in the MD F was calculated using formula (2).
[0084]
number
number
[0085] The 1601 cm -1 The peak intensities A∥ and A⊥, the infrared dichroic ratio D, and the orientation degree F, as well as the average orientation degree F in the thickness direction for each slice, are shown in Table 1. In addition, Fig. 4 is a graph showing the orientation degree F for each position of the measurement region in slices of the liquid crystal polymer films of the untreated film, the Example, and the Comparative Example 2.
[0086] [Table 1]
[0087] As shown in Table 1 and FIG. 4, the slices of the liquid crystal polymer film of Example 1 and Comparative Example 2 had a lower degree of orientation F in the entire thickness direction compared to the slices of the untreated liquid crystal polymer film. When the slices of the liquid crystal polymer film of Example 1 and Comparative Example 2 were compared, the degree of orientation F of the slices of the liquid crystal polymer film of Example 1 was higher in the entire thickness direction than the slices of the liquid crystal polymer film of Comparative Example 2. In addition, unlike the slices of the liquid crystal polymer film of Comparative Example 2, the slices of the untreated and liquid crystal polymer films of Example 1 tended to have a higher degree of orientation in the measurement area located at the center in the thickness direction (distance in the thickness direction from the surface of the slice: 15 μm, 25 μm, and 35 μm) than the measurement area located at the surface side in the thickness direction (distance in the thickness direction from the surface of the slice: 5 μm and 45 μm).
[0088] [Dielectric properties of liquid crystal polymer films] The copper layer, rolled copper foil, and electrolytic copper foil were chemically etched away from the metal laminated films of Example 1, Comparative Example 1, and Comparative Example 2 with a ferric chloride solution or the like to produce liquid crystal polymer films for measuring dielectric properties of Example 1, Comparative Example 1, and Comparative Example 2. The thickness, dielectric constant, and dielectric loss tangent of the untreated liquid crystal polymer film identical to that used in producing the metal laminated films of Example 1, Comparative Example 1, and Comparative Example 2, and the liquid crystal polymer films for measuring dielectric properties of Example 1, Comparative Example 1, and Comparative Example 2 were measured. The dielectric constant and dielectric loss tangent were measured by an open resonator method using a dielectric constant / dielectric loss tangent measuring system (DPS03 manufactured by Keycom Co., Ltd.) at a measurement frequency of 28 GHz. The measurement results are shown in Table 2.
[0089] [Table 2]
[0090] As shown in Table 2, the increase in the dielectric tangent of the liquid crystal polymer film of Comparative Example 1 and Comparative Example 2 compared to the untreated liquid crystal polymer film exceeded 14%, whereas the increase in the dielectric tangent of the liquid crystal polymer film of Example 1 compared to the untreated liquid crystal polymer film was less than 5%.
[0091] [Bonding strength between metal layer and liquid crystal polymer film] For the metal laminated films of Examples 1 to 8 and Comparative Examples 1 and 2, the bonding strength between the metal layer and the liquid crystal polymer film was measured by the measurement method described in the section "A. Metal Laminated Film 3. Metal Laminated Film". For the metal laminated films of Examples 5 to 8, the carrier layer and the peeling layer of the copper foil with a carrier layer were removed to expose the ultra-thin copper layer, and then, in order to prevent the thin and fragile ultra-thin copper layer from being cut, electrolytic copper plating was applied to the surface of the ultra-thin copper layer in the same manner as in the method of applying electrolytic plating to the metal layer surface described in the section "A. Metal Laminated Film 3. Metal Laminated Film", and the bonding strength between the metal layer and the liquid crystal polymer film was measured after increasing the thickness of the ultra-thin copper layer. These measurement results are shown in Table 3.
[0092] [Table 3]
[0093] As shown in Table 3, the bonding strength between the metal layer and the liquid crystal polymer film was 2.0 N / cm or more in the metal laminated films of Examples 1 to 8. Moreover, in the metal laminated films of Examples 1 to 8, there was a tendency that the bonding strength increased as the heat treatment temperature increased. [Explanation of symbols]
[0094] 1A Metal Laminated Film 10 metal layers 12 Copper foil (metal foil) 12a Copper foil surface 14 Middle Class 14a Surface of the intermediate layer opposite to the liquid crystal polymer film side 20 Liquid crystal polymer film 20a One surface of the liquid crystal polymer film
Claims
1. Providing a liquid crystal polymer film and a metal foil; laminating an intermediate layer containing a metal on at least one surface of the liquid crystal polymer film; activating the surface of the intermediate layer by sputter etching; activating the surface of the metal foil by sputter etching; roll-bonding the activated surfaces of the intermediate layer and the metal foil together at a rolling reduction of 0 to 30%; a step of subjecting the roll-bonded intermediate layer, the metal layer having the metal foil, and the liquid crystal polymer film to a heat treatment at a temperature of the melting point of the liquid crystal polymer film -100°C or more and the melting point -10°C or less; Equipped with The method for producing a metal laminated film, wherein the degree of orientation F at the central portion in the thickness direction of the liquid crystal polymer film after the heat treatment is 0.31 or more.
2. A method for manufacturing a liquid crystal polymer film, comprising the steps of: preparing a liquid crystal polymer film and a metal foil; laminating an intermediate layer containing a metal on at least one surface of the liquid crystal polymer film; activating the surface of the intermediate layer by sputter etching; activating the surface of the metal foil by sputter etching; roll-bonding the activated surfaces of the intermediate layer and the metal foil together at a rolling reduction of 0 to 30%; a step of subjecting the roll-bonded intermediate layer, the metal layer having the metal foil, and the liquid crystal polymer film to a heat treatment at a temperature of the melting point of the liquid crystal polymer film -100°C or more and the melting point -10°C or less; Equipped with A method for producing a metal laminated film, characterized in that the orientation degree F of the thickness direction central portion of the liquid crystal polymer film after the heat treatment is 77% or more of the orientation degree F of the thickness direction central portion of the liquid crystal polymer film before the metal layer is laminated.
3. 3. The method for producing a metal laminated film according to claim 1, wherein the dielectric tangent of the liquid crystal polymer film after the heat treatment is less than 114% of the dielectric tangent of the liquid crystal polymer film before the metal layer is laminated thereon.
4. A method for manufacturing a metal laminated film described in any one of claims 1 to 3, characterized in that the average thickness direction orientation degree F of the liquid crystal polymer film after the heat treatment is 0.31 or more.
5. A method for manufacturing a metal laminated film described in any one of claims 1 to 4, characterized in that the bonding strength between the metal layer and the liquid crystal polymer film after the heat treatment is 2.0 N / cm or more.
6. A method for producing a metal laminated film described in any one of claims 1 to 5, characterized in that the intermediate layer contains any one of metals selected from the group consisting of copper, iron, nickel, zinc, chromium, cobalt, titanium, tin, platinum, silver, and gold, or an alloy containing such a metal.
7. A method for producing a metal laminated film as described in claim 6, characterized in that the intermediate layer contains copper or an alloy containing copper.
8. A method for producing a metal laminated film described in any one of claims 1 to 7, characterized in that the metal foil is copper foil, copper alloy foil, or copper foil with a carrier.
Citation Information
Patent Citations
Phase scanning array antenna
JP1979011656A
Coating method using polymer film and manufacture of metal foil laminated body
JP1999348178A
High-frequency circuit board
JP2000269616A
Multilayer metal laminate film and its manufacturing method
JP2002113811A
Conductive layer-laminated material and part using the material
JP2003136626A